The intervention of Lavender Aroma Therapy to Reduce the Pain Intensity of Dysmenorrhea In Adolescent - Intan Kumalasari; Bambang Soewito; Maliha Amin; Maksuk; Viona Ovaliandari (Chakra Brahmanda Lentera Institute, 2022)
Background: dysmenorrhea is a common problem for women in Indonesia and the world. According to WHO (2017) it is estimated that 90% of women worldwide have experienced dysmenorrhea, and 10-15% of them have experienced severe dysmenorrhea. This condition requires pharmacological and non-pharmacological treatment. One of them gave lavender aromatherapy. Objective: This study aims to determine the effectiveness of applying lavender aromatherapy procedures to clients with dysmenorrhea. Methods: This study used a qualitative design with a case study approach to describe in-depth information and explore clients' problems with dysmenorrhea in fulfilling their comfort needs by using lavender aromatherapy. Variable independent was lavender aroma therapy. The dependent variable was pain level. Results: Giving lavender aromatherapy for three consecutive days within ± 30 minutes as much as 2 x 1 day in the morning and evening was proven to reduce the intensity of dysmenorrhea pain in Ms. B from a scale of 6 to 1, while Ms. Ra experienced a decrease in pain intensity from a scale of 7 into 2. The difference in the final results of the decrease in pain intensity was more due to the difference in the initial pain intensity in the two patients. Conclusion: Non-pharmacological methods with lavender aromatherapy are effective in reducing the intensity of dysmenorrhea pain, so this method can be widely implemented to reduce cases of dysmenorrhea in adolescents.